(untitled) (Bangladesh Journal of Plant Taxonomy, 2012)
Fifty new combinations are proposed in Phanera for species earlier treated in Bauhinia L. DOI: http://dx.doi.org/10.3329/bjpt.v19i1.10942 Bangladesh J. Plant Taxon. 19(1): 55-61, 2012 (June)